Wednesday

April 23, 2014

April 23, 2014

Posted by **Meloney** on Wednesday, May 6, 2009 at 5:26pm.

(x+1)(x-3)=117

I simplified and got:

x^2-3x+x-3=117

x^2-2x-3=117

x^2-2x-120=0

I split the middle term and got:

x^2-12x+10x-120=0

What should I do next? I have no idea how to finish factoring this...

thanks,

meloney

- Algebra 1 -
**Reiny**, Wednesday, May 6, 2009 at 5:43pmnow you want to factor by "grouping"

x^2-12x+10x-120=0

x(x-12) + 10(x-12) = 0

((x-12)(x+10) = 0

so x= 12 or x = -10

- Algebra 1 -
**Meloney**, Wednesday, May 6, 2009 at 5:46pmwow I never would have thought of grouping them. Thanks!!!

**Related Questions**

algebra - Could you please check my answer to this problem: Simplify the ...

Hard algebra qestion - 3x^2+6x/2x^2-11x+12 - 2x^2-5x+3/x^2+x-2 ÷ 4x^2-12x+9/x^2-...

algebra - Can someone please help me with this math problem? Thanks. Let g(x)=x^...

algebra - Find the value of y for a given value of x, if x varies directly with ...

Algebra 2 - Choose the appropriate simplified expression. 1. 8x^2-10x+3/6x^2+3x-...

math - 3x^2+6x/2x^2-11x+12 - 2x^2-5x+3/x^2+x-2 ÷ 4x^2-12x+9/x^2-4 I got 3x^3+2x^...

Algebra - Here is what I am trying to factor: 2x^2 + 3x + 1 = 0. I split the ...

Axia Math 117 - I am of need of HELP. I am working on the word problems for AXIA...

math 117 - x/(x-2)- (x+1)/x= 8/(x^2-2x) notice that x^2 - 2x factors to x(x-2), ...

Algebra - Here is the problem: Given f(x)=-x^3+3x^2-2x+6, find f(-1), f(0), and ...